Relation between Obesity and Precocious Puberty a Biochemical and Radiological Test - Altaan, Esraa Azzam Sulaiman; Rasool, Abeer Mansour Abdel; Ali, Kawthar Waleed; Alkashab, Dhafar Mikdad; Tahseen, Mohammad (American Journal of Biomedicine and Pharmacy, 2025)
Background: Obesity has also increasingly been recognized as a key player in the determination of pubertal timing, and there is compelling evidence associating excess adiposity with precocious puberty, most famously in girls. Precocious puberty, i.e., development of secondary sexual characteristics at less than 8 years in girls, has been associated with endocrine dysregulation, in the form of elevated leptin, insulin resistance, and increased estrogen secretion, all contributing to premature activation of the hypothalamic-pituitary-gonadal (HPG) axis. Objective: The current study is intended to investigate the correlation between obesity and precocious puberty in biochemical markers (LH, FSH, estradiol, insulin, and leptin) and radiological assessment (assessment of bone age) in 8-9-year-old girls. Methods: A retrospective cross-sectional study was conducted in Al-Khansa Hospital, where subjects were separated into obese and non-obese categories. Blood analyses were conducted for hormonal markers, and X-ray imaging was utilized to assess bone age advancement. Statistical analysis was conducted to analyze the association between obesity and the development of early puberty. Results: Results indicate a significant correlation between precocious puberty with obesity, and 70% of the participants were found to have elevated LH, FSH, and estradiol levels, which supported premature activation of the HPG axis. Similarly, 70% had elevated fasting insulin, and 60% had elevated leptin, indicating a metabolic-hormonal association with the premature development of puberty. Radiological findings supported advanced bone age in obese children, further strengthening the hypothesis of premature pubertal development. Conclusion Early screening, hormonal evaluation, and lifestyle interventions are crucial for delaying puberty onset and reducing long-term health risks in obese children at risk of precocious puberty.